2013
DOI: 10.1002/jbm.a.34935
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nanoparticle‐embedded polymeric surfaces on cellular adhesion, proliferation, and differentiation

Abstract: The development of functional substrates to direct cellular organization is important for biomedical applications such as regenerative medicine and biorobotics. In this study, we prepared freestanding polymeric ultrathin films (nanofilms) consisting of poly(lactic acid) (PLA) and magnetic nanoparticles (MNPs), and evaluated the effects of their surface properties on the organization of cardiac-like rat myoblasts (H9c2). We changed surface properties of the PLA nanofilms (i.e., roughness and wettability) as a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Recently, biodegradable and biocompatible materials (e.g. polysaccharides or polyesters) have been proposed as soft patches for cosmetic use, as innovative alternative to traditional surgical sutures, as nanopatches on gastrointestinal wall or as flexible cell growth supports , Fujie 2007, Fujie 2009, Pensabene 2009, Ricotti 2010, Fujie 2012, Ventrelli 2014. In particular, it has been demonstrated that free-standing poly(Llactic acid) (PLLA) nanofilms can adhere tightly to skin or organs by physical adhesion (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, biodegradable and biocompatible materials (e.g. polysaccharides or polyesters) have been proposed as soft patches for cosmetic use, as innovative alternative to traditional surgical sutures, as nanopatches on gastrointestinal wall or as flexible cell growth supports , Fujie 2007, Fujie 2009, Pensabene 2009, Ricotti 2010, Fujie 2012, Ventrelli 2014. In particular, it has been demonstrated that free-standing poly(Llactic acid) (PLLA) nanofilms can adhere tightly to skin or organs by physical adhesion (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, the proliferation rate of adherent cells can be affected by nanostructured surfaces. Several studies have demonstrated that the surface roughness of the cell culture plates influences the cellular behavior [28][29][30]. Therefore, the stability of certain nanoparticle coatings (nanomaterials and nanocomposites) and the effect of potentially solved nanoparticles to the human organism may be more relevant.…”
Section: Journal Of Nanomaterialsmentioning
confidence: 99%
“…Additionally, nanofilms with MNPs showed better differentiation of cells compared to the absence of MNPs. Myotubes formation together with higher fusion index was obtained in the presence of MNPs . Similarly the micropillar patterns of polymer/Fe 3 O 4 NPs nanocomposites were fabricated via thermal embossing micro‐imprint lithography.…”
Section: Self‐assembled Monolayers Of Nanomaterials As Biomaterialsmentioning
confidence: 99%
“…Myotubes formation together with higher fusion index was obtained in the presence of MNPs. [69] Similarly the micropillar patterns of polymer/Fe 3 O 4 NPs nanocomposites were fabricated via thermal embossing micro-imprint lithography. The polymer nanocomposite showed shape memory function which can be triggered by external stimuli such as magnetic field or heat.…”
Section: Cell Adhesion On Sams Of Nanomaterialsmentioning
confidence: 99%